Britain's future in Europe, the known Plan A to remain or the unknown Plan B to leave. ([2016]) - Emerson, Michael, 1940-; Avery, Graham, 1943-; Beblavý, Miroslav; Behrens, Arno; Blockmans, Steven; Brady, Hugo; Gros, Daniel, 1955-; Hájková, Alžběta; Lannoo, Karel; Łazowski, Adam; Núñez Ferrer, Jorge; Peers, Steve; et al.
No abstract available